Effect of oral antimicrobial prophylaxis on surgical site infection after elective colorectal surgery: multicentre, randomised, double blind, placebo controlled trial. (3rd November 2022) - Futier, Emmanuel; Jaber, Samir; Garot, Matthias; Vignaud, Marie; Panis, Yves; Slim, Karem; Lucet, Jean-Christophe; Lebuffe, Gilles; Ouattara, Alexandre; El Amine, Younes; Couderc, Philippe; Dupré, Aurélien; et al.
Abstract: Objective: To investigate whether oral antimicrobial prophylaxis as an adjunct to intravenous antibiotic prophylaxis reduces surgical site infections after elective colorectal surgery. Design: Multicentre, randomised, double blind, placebo controlled trial. Setting: 11 university and non-university hospitals in France between 25 May 2016 and 8 August 2019. Participants: 926 adults scheduled for elective colorectal surgery. Intervention: Patients were randomised to receive either a single 1 g dose of ornidazole (n=463) or placebo (n=463) orally 12 hours before surgery, in addition to intravenous antimicrobial prophylaxis before surgical incision. Main outcome measures: The primary outcome was the proportion of patients with surgical site infection within 30 days after surgery. Secondary outcomes included individual types of surgical site infections and major postoperative complications (Clavien-Dindo classification grade 3 or higher) within 30 days after surgery. Results: Of the 960 patients who were enrolled, 926 (96%) were included in the analysis. The mean age of participants was 63 years and 554 (60%) were men. Surgical site infection within 30 days after surgery occurred in 60 of 463 patients (13%) in the oral prophylaxis group and 100 of 463 (22%) in the placebo group (absolute difference −8.6%, 95% confidence interval −13.5% to −3.8%; relative risk 0.60, 95% confidence interval 0.45 to 0.80). The proportion of patients with deep infections was 4.8% in the oral prophylaxis group and 8.0% in the placebo group (absolute difference −3.2%, 95% confidence interval −6.4% to −0.1%). The proportion of patients with organ space infections was 5.0% in the oral prophylaxis group and 8.4% in the placebo group (absolute difference −3.4%, −6.7% to −0.2%). Major postoperative complications occurred in 9.1% patients in the oral prophylaxis group and 13.6% in the placebo group (absolute difference −4.5%, −8.6% to −0.5%). Conclusion: Among adults undergoing elective colorectal surgery, the addition of a single 1 g dose of ornidazole compared with placebo before surgery significantly reduced surgical site infections. Trial registration: ClinicalTrials.gov NCT02618720 .